Ultimate capacity of I-sections under combined loading – Part 1: Experiments and FE model validation. (August 2018) - Yun, X.; Gardner, L.; Boissonnade, N.
Abstract: An experimental and numerical study of hot-rolled steel I-sections under combined compression and bending moment is presented herein. A total of two stub column tests and 12 mono-axial or bi-axial eccentric compression tests on HEB 160 cross-sections with two different material grades (S235 and S355) were carried out. The tested cross-sections were of stocky proportions to enable the influence of material strain hardening on the strength and behaviour of hot-rolled steel I-sections to be investigated. The loading eccentricities for the eccentric compression tests were varied in order to achieve different axial compression-to-bending moment ratios. Measured geometric and material properties, together with the full load-deformation histories from the test specimens, were reported. Finite element (FE) models were developed and validated against the experimentally obtained load-deformation curves, as well as the failure modes. The FE results successfully captured the experimental structural performance of hot-rolled steel I-sections and the validated FE models were then used for parametric studies in the companion paper to generate additional numerical results, considering different cross-section slendernesses, material grades and combinations of loading. The experimental and numerical results are employed in the companion paper for the assessment of the design rules given in EN 1993-1-1 (2005) and AISC-360-16 (2016) and for the extension of the deformation-based continuous strength method to the case of hot-rolled steel I-sections under combined loading. Highlights: An experimental programme including 12 cross-section tests on hot-rolled steel I-sections has been carried out. A range of material grades and loading combinations has been investigated. Numerical models have been established and validated against the tests results. Good agreement between the results of the FE models and tested specimens was obtained.